Production of a latex agglutination reagent for the rapid diagnosis of cryptococcal meningitis - Trovero, A. (2020)
Fil: Trovero, A. ANLIS Dr. C. G. Malbrán. Instituto Nacional de Producción de Biológicos. Servicio antígenos y antisueros; Argentina.